Nitrogen fertilization and leaf sampling criteria potato crop - de Nobile, Fabio Olivieri; Prado, Renato Mello; Spadoni, Thais Botamede (Comunicata Scientiae, 2012)
The present study aimed to determine which leave will be displayed and the time of collection of this leave. The treatments consisted on five doses of nitrogen, four times for collection sampling and three types of leaves, arranged in a randomized block design with three repetitions, totalizing one hundred and forty-four experimental units. The leaves collections took place every fifteen days at thirty, forty-five, sixty and seventy five days after budbreak (DAB), collecting the laminated / compound young leaf (first leave), newly mature (second leave) and the mature leave (third leave) from the set of terminal leaflets. For this was installed an experiment with the culture of potato (cv. Atlantic), in Barretos/SP, the period of march the june of 2010. According to this data collected in this study, the best time for collecting the leaves is at 30 days after the budbreak of the potato cultivation containing nitrogen concentrations in the leaves minus heterogeneous of plants from a fraction to another and with values R2 = 0.98 being higher to the all times of harvests. To the diagnostic leaf, the highest determination coefficient was observed in the newly mature (second leaf) with R2 = 0.98. It can be observed that the highest levels of nitrogen were found on the first leaf (39.01 kg-1). Nevertheless, the values were very heterogeneous and did not fit the curve being the second leave (newly mature) the one that best represents the nutritional status of the plant. Therefore the recommendation for nutritional diagnosis will collect the recently matured leaves (2nd leaf) 30 days after budbreak.